2020
DOI: 10.2147/dmso.s279814
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Association of Syntax Score with Levels of Lipoprotein(a) and Inflammatory Biomarkers in Patients with Stable Coronary Artery Disease and Different Low-Density Lipoprotein Cholesterol Levels</p>

Abstract: Introduction Lipoprotein(a) (Lp(a)) is associated with the severity of coronary lesions evaluated using Syntax score in patients with stable coronary artery disease (CAD). However, the effect of low-density lipoprotein cholesterol (LDL-C) levels on the association of Lp(a) levels with Syntax score remains unclear. Methods A total of 646 patients with stable CAD were enrolled in the present study. Lp(a) levels were measured with an AU5800 Chemistry Analyzer. Syntax score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Previously published works demonstrated conflicting correlations between inflammatory markers and SS that may be confounded by the presence of other CAD risk factors [43][44][45]. Our well-matched (lipid levels and other CAD risk factors) samples with different SS may have enabled us for a more precise identification of inflammatory dysfunctions in CAD patients.…”
Section: Discussionmentioning
confidence: 85%
“…Previously published works demonstrated conflicting correlations between inflammatory markers and SS that may be confounded by the presence of other CAD risk factors [43][44][45]. Our well-matched (lipid levels and other CAD risk factors) samples with different SS may have enabled us for a more precise identification of inflammatory dysfunctions in CAD patients.…”
Section: Discussionmentioning
confidence: 85%
“…A standard lipid panel containing high levels of TG, high non-high-density lipoprotein cholesterol (non-HDL-C) and low HDL-cholesterol (HDL-C) is correlated to a high risk of CVD. More comprehensive lipid testing identified an increased levels of small dense LDL particles and remnant lipoproteins as particularly atherogenic ones [ 42 ]. Moreover, Xu’s research group reported the association of Lp(a) level with SYNTAX score, which was maintained for the group with LDL-C values over 100 mg/dL (2.586 mmol/L) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…More comprehensive lipid testing identified an increased levels of small dense LDL particles and remnant lipoproteins as particularly atherogenic ones [ 42 ]. Moreover, Xu’s research group reported the association of Lp(a) level with SYNTAX score, which was maintained for the group with LDL-C values over 100 mg/dL (2.586 mmol/L) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in individuals with established ST-elevation MI, very high (>135 mg/dL) levels of Lp(a) can predict the worse long-term outcomes as proven by the prospective cohort studies, highlighting the need for Lp(a)-based risk stratification in these patients (39). Combining Lp(a) with other risk estimates such as fibrinogen, Syntax Score etc have been shown to increase the prediction of cardiovascular events in acute or chronic ASCVD states (40,41). Even slightly elevated Lp(a) levels may result in early loss of vein grafts in the first year of the coronary artery bypass grafting surgery (42) Lp(a) levels have been shown predict mid and long term ASCVD events in patients undergoing percutaneous coronary intervention (PCI) (43).…”
Section: Clinical Implications Of High Lp(a)mentioning
confidence: 99%